Elevated H3K18 acetylation in airway epithelial cells of asthmatic subjects. Issue 1 (December 2015) - Stefanowicz, Dorota; Lee, Ja; Lee, Kevin; Shaheen, Furquan; Koo, Hyun-Kyoung; Booth, Steven; Knight, Darryl; Hackett, Tillie-Louise
Abstract Background Epigenetic adjustments of the chromatin architecture through histone modifications are reactive to the environment and can establish chromatin states which are permissive or repressive to gene expression. Epigenetic regulation of gene expression is cell specific and therefore, it is important to understand its contribution to individual cellular responses in tissues like the airway epithelium which forms the mucosal barrier to the inhaled environment within the lung. The airway epithelium of asthmatics is abnormal with dysregulation of genes such as epidermal growth factor receptor (EGFR), the ΔN isoform of the transcription factor p63 (ΔNp63), and signal transducer and activator of transcription 6 (STAT6), integral to differentiation, proliferation, and inflammation. It is important to establish in diseases like asthma how histone modifications affect tissue responses such as proliferation and differentiation. Objectives To characterize the global histone acetylation and methylation status in the epithelium of asthmatic compared to healthy subjects and to identify the impact of these variations on genes involved in epithelial functions. Methods Whole lungs were obtained from healthy and asthmatic subjects (n = 6) from which airway epithelial cells (AECs) were isolated and airway sections were taken for analysis of histone lysine acetylation and methylation by immunohistochemistry. AECs were subjected to chromatin immunoprecipitation (ChIP) using anti-H3K18ac and anti-H3K4me2 antibodies followed by RT-PCR targeting ΔNp63, EGFR, and STAT6. AECs were also treated with TSA and changes in ΔNp63, EGFR, and STAT6 expression were determined. Results We identified an increase in the acetylation of lysine 18 on histone 3 (H3K18ac) and trimethylation of lysine 9 on histone 3 (H3K9me3) in the airway epithelium of asthmatic compared to healthy subjects. We found increased association of H3K18ac around the transcription start site of ΔNp63, EGFR, and STAT6 in AECs of asthmatics. However, we were unable to modify the expression of these genes with the use of the HDAC inhibitor TSA in healthy subjects. Discussion The airway epithelium from asthmatic subjects displays increased acetylation of H3K18 and association of this mark around the transcription start site of ΔNp63, EGFR, and STAT6. These findings suggest a complex interaction between histone modifications and gene regulation in asthma.